Peran Pemerintah dalam Pelestarian Kampung Adat Cireundeu - Firda Azijah; Ayu Amalia; Mutia Nurfajar; Agung Suharja Sitanggang; Cindi Lukita (Universitas Medan Area, 2022)
The COVID-19 pandemic in Indonesia since March 2020 has had a major impact on various sectors such as the economy, health, tourism, education, and offices. The same thing also has an impact on the Cireundeu Traditional Village which has advantages and uniqueness that can attract tourists to visit. However, three months later, tourists began to come back with the health protocol provided at the Cireundeu Traditional Village. The uniqueness and advantages of the Cireundeu Traditional Village can also be seen from the economy which has absolutely no impact due to the Covid-19 pandemic. This raises the question of whether there is a role for local governments in helping the preservation of the Cireundeu Traditional Village? This study aims to describe the activities of the Student Creativity Program (PKM), explain in depth and detail the role of the government in preserving the Cireundeu Traditional Village, and explain the obstacles to implementing the Student Creativity Program (PKM) activities. Qualitative approach with descriptive-analytical method is used to obtain precise results. In analyzing the results of this research, we use Inu Kencana Syafiie's theory, namely regarding the role of the government as a regulator, dynamist, and facilitator. However, Inu Kencana Syafiie's theory regarding the role of the government still has shortcomings in more specific aspects, this is motivated by the influence of informants who do not convey in full, both data and documents.